Монастырская братва - Макеев Алексей Викторович (Русский бестселлер, 2013)
Экземпляры: ф.6 (20171227) / Инвентарный номер: 2217 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 15 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44